Evidence of novel miR-34a-based therapeutic approaches for multiple myeloma treatment - Zarone, Mayra Rachele; Misso, Gabriella; Grimaldi, Anna; Zappavigna, Silvia; Russo, Margherita; Amler, Evzen; Di Martino, Maria Teresa; Amodio, Nicola; Tagliaferri, Pierosandro; Tassone, Pierfrancesco; Caraglia, Michele (Scientific reports, 2017)
MiR-34a acts as tumor suppressor microRNA (miRNA) in several cancers, including multiple myeloma (MM), by controlling the expression of target proteins involved in cell cycle, differentiation and apoptosis. Here, we have investigated the combination between miR-34a and γ-secretase inhibitor (γSI), Sirtinol or zoledronic acid (ZOL) in order to enhance the inhibitory action of this miRNA on its canonical targets such as Notch1 and SIRT1, and on Ras/MAPK-dependent pathways. Our data demonstrate that miR-34a synthetic mimics significantly enhance the anti-tumor activity of all the above-mentioned anti-cancer agents in RPMI 8226 MM cells. We found that γSI enhanced miR-34a-dependent anti-tumor effects by activating the extrinsic apoptotic pathway which could overcome the cytoprotective autophagic mechanism. Moreover, the combination between miR-34a and γSI increased the cell surface calreticulin (CRT) expression, that is well known for triggering anti-tumor immunological response. The combination between miR-34a and Sirtinol induced the activation of an intrinsic apoptotic pathway along with increased surface expression of CRT. Regarding ZOL, we found a powerful growth inhibition after enforced miR-34a expression, which was not likely attributable to neither apoptosis nor autophagy modulation. Based on our data, the combination of miR-34a with other anti-cancer agents appears a promising anti-MM strategy deserving further investigation.
Keywords: apoptóza; Cell Line, Tumor; kyselina zoledronová; Apoptosis; Cell Cycle; lidé; Antineoplastic Agents; Naphthols; protinádorové látky; mnohočetný myelom; buněčný cyklus; Benzamides; benzamidy; mikro RNA; Zoledronic Acid; MicroRNAs; Multiple Myeloma; naftoly; nádorové buněčné linie; Humans